Andropause: The Male Climacterium (TAJ: Journal of Teachers Association, 2009)
Andropause is a clinical condition characterized by a partial deficiency of androgens in blood and/or a decreased sensitivity in target tissues. This state of hypogonadism leads to a decline of physical energy, an altered state of well-being, a sexual dysfunction and various metabolic alterations. These issues may have deleterious effects on muscle mass, bone density, lipid profile and eventually cognitive functions. The diagnosis of andropause depends mainly on clinical features and laboratory investigations. Awareness about this condition may help to diagnosis it earlier.   doi: 10.3329/taj.v21i1.3228 TAJ 2008; 21(1): 87-92